Addressing the Shortage of GLP-1 RA and Dual GIP/GLP-1 RA-Based Therapies—A Systematic Review - Velimir Altabas; Zrinka Orlović; Maja Baretić (Diabetology)
Introduction: Glucagon-like peptide-1 receptor agonists (GLP-1 RAs) and dual glucose-dependent insulinotropic peptide/glucagon-like peptide-1 receptor agonists (GIP/GLP-1 RAs) have transformed disease management, particularly in diabetes and obesity. However, recent shortages have disrupted patient care. This review explores the current evidence regarding their direct impact on patient populations and reviews the mitigation strategies recommended by relevant health organizations. Materials and Methods: We systematically searched PubMed, Scopus, and Web of Science for studies published from the earliest available data to 10 January 2025, using these terms: “GLP-1 AND shortage”, “liraglutide AND shortage”, “dulaglutide AND shortage”, “semaglutide AND shortage”, “exenatide AND shortage”, and “tirzepatide AND shortage”. Eligible studies needed to report measurable outcomes like prescription counts, specific laboratory findings, or the proportion of a study population achieving a defined outcome related to the shortage. Only English-language clinical research was considered, while other manuscripts were not included. The risk of bias was assessed using the Critical Appraisal Skills Programme checklist. Study characteristics and findings were summarized in tables. Results: Out of 295 identified manuscripts, 85 works were retained for further screening. Consequently, 8 studies met the inclusion criteria, covering 1036 participants with type 2 diabetes and 573 treated for obesity. In addition, two studies reported prescription prevalence, and one examined prescription counts. Key findings included reduced prescription rates and shifts in treatment practices. No studies assessed impacts on cardiovascular, renal outcomes, or mortality. Discussion and Conclusions: Evidence on the health effects of these shortages is limited. Existing studies highlight disruptions in diabetes and obesity care, but broader impacts remain unclear. Preventing future shortages requires coordinated efforts among all stakeholders. Therefore, we advocate for ethical planning, sustainable production, and fair distribution strategies to mitigate long-term consequences.